(untitled) (Medical Forum Monthly, 2024)
A discoloured non vital tooth (NVT) especially in the anterior region is a common aesthetic concern for many patients, significantly impacting their self-esteem, confidence, social interactions, and employability. Effectively managing NVT, often involves the use of bleaching agents such as sodium perborate and hydrogen peroxide. The careful selection of the bleach and the application of an appropriate bleaching technique are crucial for conservative and successful case management. Improper technique can lead to complications such as cervical resorption, ultimately resulting in tooth loss. This case report aims to elucidate the proper management of a discoloured anterior tooth following endodontic treatment for a patient who reported at the Endodontic department at college of dentistry, Riphah International University, Islamabad, Pakistan in May, 2018.